Pengsahan Perkawinan di Pengadilan Agama Surabaya : (Penetapan Nomor 2540/Pdt.P/2024/PA.Sby) - Anisa Putri Wardani; Indah Purbasari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The validation of marriage is an examination of the bond between a man and a woman as life partners that has been carried out in accordance with the teachings of Islam, and the fulfillment of the elements and requirements for the validity of the marriage bond, but has not yet been registered with the relevant authorities. This study focuses on the analysis of the Surabaya Religious Court decision number 2540/Pdt.P2024/PA.Sby. This paper discusses the legal basis and requirements for the validation of marriage that were considered by the judge in making the decision to validate the marriage.